Dexmedetomidine inhibits mitochondria damage and apoptosis of enteric glial cells in experimental intestinal ischemia/reperfusion injury via SIRT3-dependent PINK1/HDAC3/p53 pathway - Qin Zhang (BMC, 2021)
Abstract Background Intestinal ischemia/reperfusion (I/R) injury commonly occurs during perioperative periods, resulting in high morbidity and mortality on a global scale. Dexmedetomidine (Dex) is a selective α2-agonist that is frequently applied during perioperative periods for its analgesia effect; however, its ability to provide protection against intestinal I/R injury and underlying molecular mechanisms remain unclear. Methods To fill this gap, the protection of Dex against I/R injury was examined in a rat model of intestinal I/R injury and in an inflammation cell model, which was induced by tumor necrosis factor-alpha (TNF-α) plus interferon-gamma (IFN-γ) stimulation. Results Our data demonstrated that Dex had protective effects against intestinal I/R injury in rats. Dex was also found to promote mitophagy and inhibit apoptosis of enteric glial cells (EGCs) in the inflammation cell model. PINK1 downregulated p53 expression by promoting the phosphorylation of HDAC3. Further studies revealed that Dex provided protection against experimentally induced intestinal I/R injury in rats, while enhancing mitophagy, and suppressing apoptosis of EGCs through SIRT3-mediated PINK1/HDAC3/p53 pathway in the inflammation cell model. Conclusion Hence, these findings provide evidence supporting the protective effect of Dex against intestinal I/R injury and its underlying mechanism involving the SIRT3/PINK1/HDAC3/p53 axis.